1991
DOI: 10.1001/jama.1991.03470140059024
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Controlled Analgesia

Abstract: --The routine use of a continuous opioid infusion in combination with a standard PCA regimen does not improve pain management compared with PCA alone after abdominal hysterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…It is clear that opioids function as a negative reinforcer (i.e., decreasing pain) in non-drug abusing populations; both males and females reliably self-administer opioids after painful medical procedures (Berman et al, 1990; Parker et al, 1991). Pain also can alter the pharmacodynamic effects of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that opioids function as a negative reinforcer (i.e., decreasing pain) in non-drug abusing populations; both males and females reliably self-administer opioids after painful medical procedures (Berman et al, 1990; Parker et al, 1991). Pain also can alter the pharmacodynamic effects of opioids.…”
Section: Introductionmentioning
confidence: 99%
“…Human laboratory studies (Comer, Sullivan, Vosburg, Kowalczyk, & Houser, 2010; Zacny et al, 1996) and clinical studies reporting patient-controlled analgesia procedures (Gil, Ginsberg, Muir, Sykes, & Williams, 1990; Graves, Arrigo, Foster, Baumann, & Batenhorst, 1985; Parker, Holtmann, & White, 1991; Sidebotham, Dijkhuizen, & Schug, 1997) indicate that non drug-abusers self-administer prescription opioids only in the presence of experimentally-induced or current pain while recreational opioid users self-administer opioids (e.g., oxycodone) regardless of the presence or absence of pain (Comer, et al, 2010; Lofwall, Nuzzo, & Walsh, 2012). These findings suggest that the reinforcing effects of opioids in pain patients is most likely due to the ability of these drugs to relieve pain, yet the abuse liability of opioids appears not to vary as a function of pain among drug users and chronic pain patients with a long history of opioid use.…”
mentioning
confidence: 99%
“…It was reported that continuous drug perfusion and PCA is superior to conventional intermittent doses of analgesics, 12) however, other researchers, 13) noted in their report that such a comment still needs further investigations. Some researchers compared epidural route and the above mentioned method and noted that there exists no diŠerence in e‹ciency, but former route is more advantageous for additional doses and that both methods are superior to intermittent dosing.…”
Section: Discussionmentioning
confidence: 90%
“…7,9,12,13) However, most of those reports were designed to compare diŠerent routes of administration of one or two agents.…”
Section: Discussionmentioning
confidence: 99%